Peningkatan Kualitas Pembelajaran Mengaji dan Optimalisasi Peran Guru Serta Orang Tua Melalui Pendekatan Digital Dan Non-digital [Enhancing the Quality of Qur’an Learning and Optimizing the Roles of Teachers and Parents Through Digital and Non-digital Approaches] - Rulyansah, Afib; Djazilan, M. Sukron; Yudianto, Firman; Maknunah, Fiena Barieroh (Indonesia Berdaya, 2025)
Abstract. Low motivation and quality in Qur’an learning at elementary schools in Yosowilangun District, Lumajang, present a major challenge for strengthening Islamic religious education. An initial survey showed that only 42% of students have a high interest in Qur’an learning, while teacher and parent involvement in the learning process remains minimal and the utilization of technology is not yet optimal. This program aims to increase students’ motivation and learning outcomes in Qur’an studies, strengthen the competencies of teachers and parents in guidance, and optimize the use of both digital and non-digital technologies within the educational ecosystem. Implementation methods include intensive training for teachers and parents, the application of gamification, Islamic storytelling, the use of AI-based digital applications, and the development of an online student progress monitoring system. Program results show a significant increase in student learning motivation, teachers’ pedagogical competence, and parental involvement in supporting Qur’an learning at home. Additionally, the use of educational technology successfully expands the variety of learning methods and facilitates student progress monitoring. The program’s impact is evident not only in academic aspects but also in strengthening Qur’anic literacy culture and creating synergy among schools, families, and technology. This multidimensional contribution is expected to serve as an innovative model for the development of digital and collaborative religious learning in elementary schools, while also reinforcing the moral and religious foundations of the young generation in Yosowilangun sustainably. Abstrak. Rendahnya motivasi dan kualitas pembelajaran mengaji di sekolah dasar wilayah Kecamatan Yosowilangun Lumajang menjadi tantangan utama bagi penguatan pendidikan agama Islam. Survei awal menunjukkan hanya 42% siswa berminat tinggi dalam belajar mengaji, sementara keterlibatan guru dan orang tua dalam proses pembelajaran masih minim, serta pemanfaatan teknologi yang belum optimal. Program ini bertujuan meningkatkan motivasi dan hasil belajar mengaji siswa, memperkuat kompetensi guru serta orang tua dalam pendampingan, dan mengoptimalkan penggunaan teknologi digital maupun non-digital dalam ekosistem pendidikan. Metode pelaksanaan meliputi pelatihan intensif bagi guru dan orang tua, penerapan gamifikasi, storytelling Islami, penggunaan aplikasi digital berbasis AI, serta pengembangan sistem pemantauan perkembangan siswa secara daring. Hasil pelaksanaan program menunjukkan adanya peningkatan signifikan pada motivasi belajar siswa, kompetensi pedagogis guru, serta keterlibatan orang tua dalam mendampingi anak mengaji di rumah. Selain itu, penggunaan teknologi pendidikan berhasil memperluas variasi metode pembelajaran dan memudahkan monitoring perkembangan siswa. Dampak program tidak hanya terlihat pada aspek akademik, tetapi juga pada penguatan budaya literasi Al-Qur’an dan terciptanya sinergi antara sekolah, keluarga, dan teknologi. Kontribusi multidimensional ini diharapkan dapat menjadi model inovatif bagi pengembangan pembelajaran agama berbasis digital dan kolaboratif di lingkungan sekolah dasar, sekaligus memperkuat fondasi moral dan religius generasi muda di Yosowilangun secara berkelanjutan.